Prototype campaign assessment of disturbance-induced tree loss effects on surface properties for atmospheric modeling (2017)
ABSTRACT: Changes in large-scale vegetation structure triggered by processes such as deforestation, wildfires, and tree die-off alter surface structure, energy balance, and associated albedo—all critical for land surface models. Characterizing these properties usually requires long-term data, precluding characterization of rapid vegetation changes such as those increasingly occurring in the Anthropocene. Consequently, the characterization of rapid events is limited and only possible in a few specific areas. We use a campaign approach to characterize surface properties associated with vegetation structure. In our approach, a profiling LiDAR and hemispherical image analyses quantify vegetation structure and a portable mast instrumented with a net radiometer, wind–humidity–temperature stations in a vertical profile, and soil temperature–heat flux characterize surface properties. We illustrate the application of our approach in two forest types (boreal and semiarid) with disturbance-induced tree loss. Our prototype characterizes major structural changes associated with tree loss, changes in vertical wind profiles, surface roughness energy balance partitioning, a proxy for NDVI (Normalized Differential Vegetation Index), and albedo. Multi-day albedo estimates, which differed between control and disturbed areas, were similar to tower-based multiyear characterizations, highlighting the utility and potential of the campaign approach. Our prototype provides general characterization of surface and boundary-layer properties relevant for land surface models, strategically enabling preliminary characterization of rapid vegetation disturbance events.